Respostas
respondido por:
2
Vamos agora fazer uma mudança de variável. Seja
Logo:
Vamos resolver a equação:
6k² - k - 1 = 0
Δ = (-1)² - 4(6)(-1) = 1 + 24 = 25
√Δ = 5
k₁ = [ - (-1) + 5 ] / 2(6) = 1+5 / 12 = 6/12 = 1/2 = 2⁻¹
k₂ = [ - (-1) - 5 ] / 2(6) = 1-5 / 12 = -4 / 12 = -1/3 = -3⁻¹
Logo, k = 2⁻¹ ou k = -3⁻¹
1)
(ABSURDO!)
2)
3)
Logo, x = -1
Conjunto solução = S = {-1}
belaroseta:
vlw mesmi
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás